An IR820 Dye–Protein Complex for Second Near‐Infrared Window and Photoacoustic Imaging. Issue 4 (18th December 2019) - Du, Bulin; Qu, Chunrong; Qian, Kun; Ren, Ying; Li, Yesen; Cui, Xiaohong; He, Shuqing; Wu, Yifan; Ko, Timothy; Liu, Ruiqi; Li, Xuena; Li, Yaming; et al.
Abstract: Recently, much attention has been focused on the development of second near‐infrared window (NIR‐II, 1000–1700 nm) fluorescence imaging because of its reduced scattering, minimal absorption, and negligible autofluorescence. NIR‐II bioimaging allows the visualization of deep anatomical features with an unprecedented degree of clarity. In addition to the construction of a variety of new NIR‐II fluorophores, using a fluorescence tail emission greater than 1000 nm for conventional NIR‐I dyes represents a promising strategy for developing an NIR‐II imaging technique. Herein, the authors report tailoring a supramolecular assembly of human serum albumin (HSA) protein complexed with a sulfonated NIR‐I organic dye (IR820) to produce a brilliant 21‐fold increase in fluorescence for NIR‐II imaging. In vivo NIR‐II imaging with IR820–HSA allows noninvasive and dynamic visualization and monitoring of physiological and pathological conditions of the vascular system, lymphatic drainage system, and tumor‐bearing mice, as well as image‐guided tumor resection with high spatial and temporal resolution. Furthermore, photoacoustic imaging (PAI) of IR820–HSA in mouse tumor models also demonstrate good tumor accumulation. Overall, an IR820–protein complex with high biocompatibility can be easily constructed using a conventional NIR‐I dye that provides a new theranostic tool with high clinical translation potential. Abstract : After mixing with HSA, fluorescence in the biological NIR‐II window of the IR820–HSA organic complex increases dramatically. In vivo NIR‐II imaging with IR820–HSA can noninvasively and dynamically be used to visualize and monitor the physiological and pathological conditions of the vascular system, lymphatic drainage system, and tumor‐bearing mice, as well as to allow image‐guided tumor resection.